Cost Comparison For Non-Seismic And Seismic Design Of A Rectangular Building Structure Located On Different Soil Types Based On Malaysian Annex - Toh, Wei Jian (Universiti Sains Malaysia, 2021)
Malaysia is situated in an earthquake-free zone. However, due to incidents that questioned the integrity of the existing buildings that were designed without considering seismic load, the construction industry in Malaysia will be adopting Malaysian National Annex (NA) to Eurocode 8 (EC 8). However, there is limited information on the material cost change if earthquake resistant design implemented in Malaysia. Objective of this study are to determine the cost difference between building structure with seismic and non- seismic design and to evaluate the effect of different soil type to the overall material cost of the main building structural frame. Five types of RC building frame categorised as 10 storeys, 15 storeys, 20 storeys, 25 storeys and 30 storeys were analysed and designed using ETABS software. The reinforced concrete building designed based on EC 2 and redesigned according to EC 8 with peak ground acceleration, αgR 0.06g reflecting the low seismic zone in Malaysia for ductility class low (DCL) and also with soil type A, D and E which reflecting the common soil type in Malaysia. The results showed that overall cost for building models situated on soil type A and subjected to seismic load decreased in the range of 3% - 13% compared to the non-seismic design. Soil type D showed an increase in the percentage difference from 10 storeys until 25 storeys, which is in the range of 2% - 15%. After 25 storeys, the percentage difference of cost of material was found to reduce by 2% for 30 storeys. Other than that, soil type E showed an increase in the percentage difference from 10 storeys until 20 storeys, which is in the range of 0% - 8%. The percentage difference of cost of material tends to reduce by 3% -7 % on 25 storeys onward. This is due to the significant wind load effect on high-rise building. It can be concluded that building models situated soil type D showed the highest increase in the cost among the soil types compared to non-seismic design due to the high value of base shear force, Fb and spectral acceleration at the fundamental period T1.